Zebrafish as a model for studying the developmental neurotoxicity of propofol. Issue 12 (23rd June 2015) - Guo, Peipei; Huang, Zhibin; Tao, Tao; Chen, Xiaohui; Zhang, Wenqing; Zhang, Yiyue; Lin, Chunshui
Abstract Anesthetics can cause widespread apoptotic neurodegeneration and adverse effects on synaptogenesis during early postnatal life. Synaptogenesis correlates with several proteins, including myelin basic protein (MBP). However, little is known about the adverse effects of exposure to propofol on MBP, particularly during embryonic development. Our goal was to use zebrafish to explore the effect of propofol on embryonic development, apoptosis and MBP expression. Zebrafish embryos were exposed to propofol at defined doses and stages from 6 to 48 h postfertilization by immersion. The survival rate, hatchability, aberration rate, cell apoptosis and gene expression were analyzed at defined stages. Analysis revealed that doses of 1, 2 and 3 µg ml–1 propofol were reasonable anesthetic concentrations for zebrafish embryos. These doses of propofol caused a significant decrease in hatchability and an increase in aberration rate. Moreover, 6 days postfertilization (dpf) larvae are anesthetized by immersion into water containing 1, 2 or 3 µg ml–1 of propofol. The number of apoptotic cells in the head of propofol‐treated 36 h postfertilization embryos were significantly increased, and the expression of caspases‐3, ‐8 and ‐9 were upregulated. Apoptosis was also induced in the brain of 3 dpf larvae exposed to propofol. However, propofol caused a decrease in mbp gene and protein (dose‐dependent) expression levels in the central nervous system of 3 dpf zebrafish. These data show that embryonic exposure to propofol is neurotoxic, causing increased apoptosis and decreased MBP expression. We believe zebrafish can be used as a novel model to explore the mechanisms of propofol neurotoxicity. Copyright © 2015 John Wiley & Sons, Ltd.